Eira Llwyd - Evans-Jones, Gareth (Gwasg Pantycelyn, 2018)
A subtle and moving short novel which follows the lives of three Jews imprisoned in Nazi concentration camps during the Holocaust. Intro – Hawlfraint – Eira Llwyd – Pluo – Arbeit – macht – frei – Rhith y gannwyll – Diolchiadau.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books